Label-free analysis of physiological hyaluronan size distribution with a solid-state nanopore sensor - Felipe Rivas (Nature Portfolio, 2018)
Involved in various diseases, hyaluronic acid is an important indicator of pathophysiology. Here, the authors report on a solid-state nanopore for the detection of the molecular weight and abundance of hyaluronic acid and demonstrate the system by studying an equine model of osteoarthritis